2016
DOI: 10.1038/ejcn.2015.230
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an updated evidence-based protocol for proactive gastrostomy tube insertion in patients with head and neck cancer

Abstract: The results of this study confirm that the updated high-risk category in the protocol for the swallowing and nutrition management of patients with head and neck cancer remains valid to predict proactive gastrostomy in a mixed population receiving helical intensity-modulated radiotherapy and 3-D conformal radiotherapy. The protocol has an improved sensitivity and specificity and hence remains just as relevant for advanced techniques of radiation treatment delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 50 publications
2
46
0
Order By: Relevance
“…Of the 181 that were deemed low risk, 18% (n=32) were deemed to have been candidates for a proactive gastrostomy and 82% (n=149) were correctly identified to not require a proactive gastrostomy (true negatives). Thus the protocol has a high sensitivity and specificity and a high positive predictive value (92%) in classifying those who would benefit from a proactive gastrostomy (Brown et al, 2016b). Age was not found to be associated with the outcome "met criteria for proactive gastrostomy" (p=0.463), however smoking status was associated (p=0.041).…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…Of the 181 that were deemed low risk, 18% (n=32) were deemed to have been candidates for a proactive gastrostomy and 82% (n=149) were correctly identified to not require a proactive gastrostomy (true negatives). Thus the protocol has a high sensitivity and specificity and a high positive predictive value (92%) in classifying those who would benefit from a proactive gastrostomy (Brown et al, 2016b). Age was not found to be associated with the outcome "met criteria for proactive gastrostomy" (p=0.463), however smoking status was associated (p=0.041).…”
Section: Resultsmentioning
confidence: 78%
“…Whilst we have previously shown the guidelines in their current format have a high validity (Brown et al, 2016b), this study has confirmed that the two key variables of tumour site and treatment are strongly associated to a number of other clinical variables, thus eliminating the need to include any additional variables which would unnecessarily add to the complexity of the high risk criteria definition. The significance of tumour site is expected given the role of the pharynx in the swallowing process.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations